School Readiness on The Implementation of Learning Delivery Modalities (LDM’s) in The City Schools Division Province of Laguna: An Input to Curriculum Policy Brief and Intervention Program (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
This study aimed to determine the relationship between the level of implementation of learning delivery modalities (LDMs) and School Readiness using 7s Model for its implementation in the City Schools Division, Province of Laguna. This study employs the descriptive method of research, specifically the descriptive correlation. It is intended to investigate the correlation between the variables. A stratified sampling method was utilized to select the respondents from the population of teachers and school heads. A survey questionnaire was the primary data gathering instrument of the study. Results of the study show that there is a significant relationship between the post-implementation of the three different distance learning delivery modalities to the 7S McKinsey organizational tools. The results entail that prior to the implementation of the different learning delivery modalities, the schools have provided professional development training that will improve and maximize the competencies and skills of the teachers. It means that the teachers at present were also equipped with the necessary skills needed to face the challenges brought by this pandemic. On the other hand, it also shows that there are teachers who observed that some of the assignments/tasks given to them are not appropriate in some other aspects. The school may provide a copy of teachers' job descriptions for them to be well-informed about their duties and responsibilities. The researcher recommended that the Division Office may conduct training that will further explain the process of utilizing 7S McKinsey Organizational Tools so that the school may enhance and maximize the use of this organizational tool to strengthen the implementation of the different learning delivery modalities. It was also suggested that the school heads, together with the teachers, may carefully plan and implement strategy that will give them ease in the implementation of LDM regardless of the size of the school.